Description of 'Gorbachella massiliensis' gen. nov., sp. nov., 'Fenollaria timonensis' sp. nov., 'Intestinimonas timonensis' sp. nov. and 'Collinsella ihuae' sp. nov. isolated from healthy fresh stools with culturomics. (March 2017) - Durand, G.A.; Cadoret, F.; Lagier, J.C.; Fournier, P.E.; Raoult, D.
Abstract: We report here the main characteristics of ' Gorbachella massiliensis ' GD7 T gen. nov., sp. nov., ' Fenollaria timonensis ' GD5 T sp. nov., ' Intestinimonas timonensis ' GD4 T sp. nov., and ' Collinsella ihuae ' sp. nov. GD8 T isolated from one fresh stool of a French volunteer. We used a bacterial culturomics approach combined with taxono-genomics.